Duct modes damping through an adjustable electroacoustic liner under grazing incidence. (21st July 2018) - Boulandet, R.; Lissek, H.; Karkar, S.; Collet, M.; Matten, G.; Ouisse, M.; Versaevel, M.
Abstract: This paper deals with active sound attenuation in lined ducts with flow and its application to duct modes damping in aircraft engine nacelles. It presents an active lining concept based on an arrangement of electroacoustic absorbers flush mounted in the duct wall. Such feedback-controlled loudspeaker membranes are used to achieve locally reacting impedances with adjustable resistance and reactance. A broadband impedance model is formulated from the loudspeaker parameters and a design procedure is proposed to achieve specified acoustic resistances and reactances. The performance is studied for multimodal excitation by simulation using the finite element method and the results are compared to measurements made in a flow duct facility. This electroacoustic liner has an attenuation potential comparable to that of a conventional passive liner, but also offers greater flexibility to achieve the target acoustic impedance in the low frequencies. In addition, it is adaptive in real time to track variable engine speeds. It is shown with the liner prototype that the duct modes can be attenuated over a bandwidth of two octaves around the resonance frequency of the loudspeakers.